KINERJA KESEHATAN KOPERASI SIMPAN PINJAM (KSP) DAN UNIT SIMPAN PINJAM (USP) â€“ KOPERASI DI KOTA PONTIANAK - B2051141011, MUSTAMAR (Jurnal Ekonomi Daerah (JEDA), 2016)
The focus of this research is to acknowledge and to analize the difference between working performance condition of 5 (five) Loan and Saving Cooperatives and 25 (twenty five) Loan and Saving Cooperative Units in 2014, on 7 (seven) aspects (the capital aspect, the quality of productive asset aspect, the management aspect, the efficiency aspect, the liquidity aspect, the autonomy and growth aspect, and the identity aspect of a cooperative), with the use of the 22 indicators of working performance condition on each aspect (3 indicators for the capital aspect, 4 indicators for quality of productive asset aspect, 5 indicators for the management aspects, 3 indicators for the efficiency aspect, 2 indicators for the liquidity aspect, 3 indicators for the autonomy and growth aspect and 2 indicators for the identity aspect of a cooperative). This research is using Descriptive Statistic Method to draw conclusion. This method is used to elaborate the data that has been collected in order to know the working performence condition of Loan and Saving Cooperatives and ) Loan and Saving Cooperative Units in Pontianak. Another statistic tool that is used is variant analysis bu using the SPSS 17 system. The catagory for the evaluation of working performance condition of Loan and Saving Cooperatives and Loan and Saving Cooperative Units is based on the State Minister for Cooperatives, Small and Medium Enterprises Decree; number 14/Per/M.KUKM/XII/2009, which consist ofÂ â€œHealthyâ€, â€œQuite Healthyâ€, â€œLess Healthyâ€Â â€œNot Healthyâ€ and â€œVery Unhealthyâ€. The result of this research is different in term of score but they are all inclede in the same catagory which is â€œQuite Healthyâ€, with the scoring standard between 60 â‰¤ X <80. Â Keywords : Working Performance Condition, Capital Aspect, Quality Of Productive Asset Aspect, Management Aspect, Efficiency Aspect, Liquidity Aspect, Autonomy And Growth Aspect, And Identity Aspect Of A Cooperative